Super-soft waterproof abrasive paper and preparation method thereof

By using modified polyurethane base glue, composite modified silicon carbide abrasives and amino modified calcium carbonate phenolic resin compound glue in water sandpaper, a dense interpenetrating network structure is constructed, which solves the problems of low tensile strength, high water absorption and poor grinding performance of water sandpaper, and achieves higher longitudinal tensile strength, lower water absorption and better grinding performance.

CN119897811AActive Publication Date: 2025-04-29HEBEI SIRIEN NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411957895.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-29
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing water sandpaper has low tensile strength, high water absorption and poor grinding performance, which limits its application range.

Method used

Modified polyurethane is used as the base glue, composite modified silicon carbide is used as the abrasive, and phenolic resin containing amino modified calcium carbonate is introduced into the composite glue layer to build a dense interpenetrating network structure.

Benefits of technology

It significantly improves the longitudinal tensile strength of the sandpaper, reduces the water absorption rate, and ensures good grinding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of grinding tool materials, and particularly relates to super-soft waterproof abrasive paper and a preparation method thereof. According to the super-soft waterproof abrasive paper, the modified polyurethane is used as the primer, the composite modified carbonized material is used as the abrasive material, and the phenolic resin composite adhesive containing the amino modified calcium carbonate is matched, so that the super-soft waterproof abrasive paper is obtained, the longitudinal tensile strength of the abrasive paper is effectively improved, the water absorption rate is reduced, and good grinding performance is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of abrasive tool materials, and particularly relates to a super-soft water-treated sandpaper and a preparation method thereof. Background Art

[0002] With the continuous development of the automobile industry, the market for automotive grinding consumables has also shown a steady growth trend. These consumables play an important role in automobile manufacturing, maintenance and beauty. The global automotive grinding consumables market is growing at a rate of about 5% per year. Due to technological advances and consumers' increasing requirements for automobile appearance, this market still has a lot of room for development. In China, due to the continuous increase in the number of cars and the increasing popularity of automobile culture, the market size of automotive grinding consumables continues to expand, and it is expected to maintain steady growth in the next few years. Silicon carbide water-resistant sandpaper is an indispensable product in the production and processing of car paint. Sandpaper is mainly composed of three parts: sandpaper base, adhesive and abrasive. It is a coated abrasive formed by firmly bonding the paper base and corundum or silicon carbide abrasive together with an adhesive.

[0003] A Chinese patent (publication number CN110919559B) discloses a water-resistant sandpaper and its preparation method. The water-resistant sandpaper of the invention has good water resistance, good cutting ability, high strength, good flexibility, and the tip of the abrasive is exposed on the surface of the substrate, highlighting the self-sharpening performance of the abrasive, which can improve the sharpness and grinding efficiency of the sandpaper. After the primer is applied and the sand is planted, it is pre-dried and the abrasive is initially fixed, and then the adhesive is applied to form a stable adhesive film, which further strengthens the bonding strength between the abrasive and the abrasive, and between the abrasive and the substrate, and has high stability. However, the patent does not solve the problems of low tensile strength, high water absorption and poor grinding performance of water-resistant sandpaper in the prior art, which seriously affects its application range.

[0004] Therefore, there is an urgent need for an ultra-soft water-treated sandpaper, which improves the longitudinal tensile strength of the sandpaper, reduces the water absorption rate, and ensures good grinding performance by compounding a base glue layer, an abrasive layer and a double glue layer on a substrate and modifying the base glue layer, the abrasive layer and the double glue layer respectively. Summary of the invention

[0005] The purpose of the present invention is to provide a super-soft water-treated sandpaper and a preparation method thereof. The super-soft water-treated sandpaper is obtained by using modified polyurethane as a base glue, using composite modified carbonization as an abrasive, and combining with a phenolic resin containing amino-modified calcium carbonate to effectively improve the longitudinal tensile strength of the sandpaper, reduce the water absorption rate, and ensure good grinding performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing super soft water sandpaper, comprising the following steps: Step S1: by weight, 50-60 parts of iron sulfate pentahydrate are added to 200-300 parts of deionized water for full dissolution, then 6-10 parts of carbon nanotubes are added for ultrasonication for 40-60 minutes, and then 100-120 parts of hydrogen peroxide are added for stirring and reaction for 10-12 hours. After the reaction is completed, filter cakes are obtained by suction filtration, and the filter cakes are washed with deionized water and dried to obtain hydroxylated carbon nanotubes; 6-10 parts of the hydroxylated carbon nanotubes and 10-14 parts of isopropyl tri(dioctylphosphoyloxy) titanate are added to 180-200 anhydrous ethanol for ultrasonication for 50-60 minutes, and then reacted at 70-80° C. for 8-10 hours. After the reaction is completed, filter cakes are washed with anhydrous ethanol and dried to obtain titanate-modified carbon nanotubes; 6-10 parts of hydroxylated carbon nanotubes are dispersed in 60-80 parts of ethyl acetate, and then 30-36 parts of polyurethane are added for stirring for 2-4 hours, and dried to obtain modified polyurethane primer; Step S2: coating the surface of the latex paper with a modified polyurethane primer to obtain a latex paper with a primer layer; Step S3: Grafting silicon carbide abrasive on the surface of the base glue layer of the latex paper with a base glue layer, and obtaining the grained sandpaper with an abrasive layer after drying once; Step S4: coating the phenolic resin adhesive on the abrasive layer surface of the abrasive layer-grafted sandpaper, and obtaining the super-soft water-based sandpaper after secondary drying.

[0007] The carbon nanotubes in the modified polyurethane primer can form a physical barrier in the matrix to prevent the generation and expansion of cracks. At the same time, the surface-treated carbon nanotubes can be evenly dispersed in the matrix, acting as a "skeleton" in the matrix to provide support and stability, thereby increasing the longitudinal tensile strength.

[0008] As a preferred solution, the silicon carbide abrasive is a composite modified silicon carbide; the preparation method of the composite modified silicon carbide comprises: adding 6 to 10 parts of sodium lignin sulfonate to 400 to 500 parts of deionized water by weight to fully dissolve, then adding 10 to 20 parts of silicon carbide (average particle size is 1 to 10 μm) and stirring for 6 to 8 hours, centrifuging to collect the supernatant, and drying to obtain a primary modified silicon carbide; adding 10 to 20 parts of the primary modified silicon carbide to 200 to 300 parts of anhydrous ethanol and ultrasonically oscillating for 40 to 60 minutes, then adding 4 to 6 parts of perfluorooctyltriethoxysilane, stirring and reacting at a speed of 3000 to 4000 r / min at 40 to 50° C. for 2 to 4 hours, and after the reaction is completed, filtering, drying, and grinding to obtain the composite modified silicon carbide.

[0009] Composite modified silicon carbide uses fluorosilane coupling agent to functionally modify silicon carbide particles and introduce fluorine-containing functional groups on the surface. The fluorine-containing functional groups have extremely low surface energy, which leads to a significant decrease in surface free energy, making it difficult for water molecules to spread or adhere to the surface, effectively reducing water absorption.

[0010] As a preferred solution, the preparation method of the phenolic resin compound glue comprises: in parts by weight, 70 to 75 parts of phenolic resin, 40 to 50 parts of amino-modified calcium carbonate, 2 to 3 parts of pigment, 0.1 to 0.3 parts of coupling agent, 0.2 to 0.4 parts of penetrant, 0.2 to 0.4 parts of defoamer and 0.2 to 0.4 parts of leveling agent are mixed and stirred for 2 to 4 hours to obtain the phenolic resin compound glue.

[0011] As a preferred solution, the phenolic resin is a phenolic phenolic resin and a biphenyl phenolic resin; the mass ratio of the phenolic phenolic resin to the biphenyl phenolic resin is (1-2):1.

[0012] As a preferred scheme, the preparation method of the amino-modified calcium carbonate comprises: adding 10 to 15 parts of calcium carbonate and 4 to 6 parts of dodecyl phosphate to 120 to 150 parts of deionized water by weight, maintaining the temperature at 80 to 85° C. for 20 to 30 minutes, filtering, and drying to obtain phosphorus-containing calcium carbonate; adding 10 to 15 parts of the phosphorus-containing calcium carbonate to 50 to 60 parts of anhydrous ethanol by weight, ultrasonically dispersing for 1 to 2 hours to obtain a suspension, adding 2 to 4 parts of DL-alanine to the suspension, heating to 75 to 80° C. and stirring for 0.5 to 1 hour, and obtaining the amino-modified calcium carbonate after suction filtration, washing, and drying.

[0013] Modified calcium carbonate introduces amino groups through DL-alanine to improve the dispersibility of calcium carbonate and make the surface of sandpaper smoother. At the same time, the modified phosphate ester can combine with calcium ions on the surface of calcium carbonate to form phosphate, which ensures adhesion through partial coating, thereby obtaining good grinding performance.

[0014] As a preferred solution, the coupling agent is selected from any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane, or a combination of at least two thereof.

[0015] As a preferred solution, the penetrant is selected from any one of Span 60, Span 80, Tween 60, or a combination of at least two of them.

[0016] As a preferred solution, the defoaming agent is selected from any one of tributyl phosphate, polydimethylsiloxane, and triglycerol monostearate, or a combination of at least two thereof.

[0017] As a preferred solution, the coating amount of the modified polyurethane primer is 10-100 g / m 2 The coating amount of the phenolic resin is 30~300g / m 2 .

[0018] The second aspect of the present invention provides a super-soft water-repellent sandpaper prepared by the preparation method described in the first aspect.

[0019] In order to achieve the above object, the present invention provides the following technical solutions: Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The modified calcium carbonate is introduced into the adhesive layer of the present invention. The modified calcium carbonate contains an active amino group, which can react with the sulfonate of the composite modified silicon carbide in the abrasive layer to generate sulfonamide, and can also undergo a nucleophilic substitution reaction with the titanate in the modified polyurethane binder. With the modified calcium carbonate as a fulcrum, a dense interpenetrating network structure is constructed, which effectively improves the longitudinal tensile strength; the density of the network structure reduces the chance of water molecules contacting the material surface, reduces the absorption of water, and thus reduces the water absorption rate; in addition, the interpenetrating network structure can reduce the free movement between molecular chains and enhance the grinding performance of the material.

[0020] 2. The carbon nanotubes in the modified polyurethane primer of the present invention can form a physical barrier in the matrix to prevent the generation and expansion of cracks. At the same time, the surface-treated carbon nanotubes can be evenly dispersed in the matrix, playing a "skeleton" role in the matrix, providing support and stability, thereby increasing the longitudinal tensile strength.

[0021] 3. The composite modified silicon carbide of the present invention uses a fluorosilane coupling agent to functionally modify silicon carbide particles and introduce fluorine-containing functional groups on the surface. The fluorine-containing functional groups have extremely low surface energy, resulting in a significant decrease in surface free energy, making it difficult for water molecules to spread or adhere to the surface, effectively reducing the water absorption rate.

[0022] 4. The modified calcium carbonate of the present invention introduces amino groups through DL-alanine to improve the dispersibility of calcium carbonate, making the surface of sandpaper smoother. At the same time, the modified treatment of phosphate ester can combine with calcium ions on the surface of calcium carbonate to form phosphate, and the adhesion is ensured by partial coating, thereby obtaining good grinding performance. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The sources of some components in the embodiments and comparative examples are as follows: Latex paper, model HS001, purchased from Qifeng New Materials Co., Ltd.; Polyurethane, model AH-1610, purchased from Anhui Dawei Huatai New Material Technology Co., Ltd.; Silicon carbide I, brand 66556, average particle size 8 μm, purchased from Hebei Wenlun Metal Materials Co., Ltd.; Silicon carbide II, model CW-SiC-001, average particle size 40 nm, purchased from Shanghai Chaowei Nanotechnology Co., Ltd. Silicon carbide III, model DH-06, average particle size 38 μm, purchased from Ningxia Dehui Carbon Co., Ltd.; Phenol-type phenolic resin, brand PF-8011, purchased from Shandong Shengquan New Materials Co., Ltd.; Biphenyl phenolic resin, brand SH-5085, purchased from Shandong Shengquan New Materials Co., Ltd.; Calcium carbonate, CAS No. 471-34-1, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Pigment, item number 159, purchased from Jinan Yazhong Pigment Co., Ltd.; 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Sinopharm Chemical Reagent Co., Ltd.; 3-Aminopropyltrimethoxysilane, CAS No. 13822-56-5, purchased from Sinopharm Chemical Reagent Co., Ltd.; γ-Glycidyloxypropyltrimethoxysilane, CAS No. 2530-83-8, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Siban 60, CAS No. 1338-41-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Siban 80, CAS No. 1338-43-8, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Tween 60, CAS No. 9005-67-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Tributyl phosphate, CAS No. 126-73-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Polydimethylsiloxane, CAS No. 9006-65-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Triglycerol monostearate, CAS No. 26855-43-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Leveling agent, brand BYK-323, purchased from BYK Chemicals, Germany; Iron sulfate pentahydrate, CAS No. 142906-29-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Carbon nanotubes, CAS No. 16291-96-6, were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Isopropyl tri(dioctylphosphoyl) titanate, CAS No. 65345-34-8, purchased from Sinopharm Chemical Reagent Co., Ltd.; Sodium lignin sulfonate, CAS No. 8061-51-6, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Perfluorooctyltriethoxysilane, CAS No. 51851-37-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Dodecyl phosphate, CAS No. 12751-23-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; DL-Alanine, CAS No. 302-72-7, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0025] Example 1 This embodiment provides a method for preparing super soft water sandpaper, comprising the following steps: Preparation of composite modified silicon carbide: by weight, 10 parts of sodium lignin sulfonate are added to 500 parts of deionized water to fully dissolve, and then 20 parts of silicon carbide I (average particle size of 8 μm) are added and stirred for 8 hours, the supernatant is collected by centrifugation, and dried to obtain primary modified silicon carbide; 20 parts of the primary modified silicon carbide are added to 300 parts of anhydrous ethanol and ultrasonically oscillated for 60 minutes, and then 6 parts of perfluorooctyltriethoxysilane are added, and the reaction is stirred at 4000 r / min at 50°C for 2 hours. After the reaction is completed, the composite modified silicon carbide is filtered, dried, and ground to obtain the composite modified silicon carbide.

[0026] Preparation of phenolic resin compound glue: (1) In parts by weight, add 15 parts of calcium carbonate and 6 parts of dodecyl phosphate to 150 parts of deionized water, keep the temperature at 85°C for 20 minutes, filter, and dry to obtain phosphorus-containing calcium carbonate; in parts by weight, add 15 parts of the phosphorus-containing calcium carbonate to 60 parts of anhydrous ethanol, ultrasonically disperse for 2 hours to obtain a suspension, add 4 parts of DL-alanine to the suspension, heat it to 80°C and stir it for 0.5 hours, filter, wash and dry to obtain the amino-modified calcium carbonate. (2) In parts by weight, mix and stir 75 parts of phenolic resin (50 parts of phenolic phenolic resin and 25 parts of biphenyl phenolic resin), 50 parts of amino-modified calcium carbonate, 3 parts of pigment, 0.3 parts of 3-aminopropyltrimethoxysilane, 0.4 parts of Span 60, 0.4 parts of tributyl phosphate and 00.4 parts of leveling agent for 4 hours to obtain the phenolic resin compound glue.

[0027] Step S1: by weight, 60 parts of iron sulfate pentahydrate are added to 300 parts of deionized water to fully dissolve, then 10 parts of carbon nanotubes are added and ultrasonicated for 60 minutes, then 120 parts of hydrogen peroxide are added and stirred for reaction for 12 hours, after the reaction is completed, filter cake is obtained by suction filtration, the filter cake is washed with deionized water, and dried to obtain hydroxylated carbon nanotubes; 10 parts of the hydroxylated carbon nanotubes and 14 parts of isopropyl tri(dioctylphosphoyl) titanate are added to 200 anhydrous ethanol and ultrasonicated for 60 minutes, then reacted at 80°C for 8 hours, after the reaction is completed, filter, wash with anhydrous ethanol, and dry to obtain titanate-modified carbon nanotubes; 10 parts of hydroxylated carbon nanotubes are dispersed in 80 parts of ethyl acetate, then 36 parts of polyurethane are added and stirred for 4 hours, and dried to obtain modified polyurethane primer; Step S2: Coat the surface of the latex paper with a modified polyurethane primer, the coating amount of the modified polyurethane primer being 100 g / m 2 , obtaining latex paper with a base glue layer; Step S3: Sand-planting the composite modified silicon carbide abrasive on the surface of the base glue layer of the latex paper with a base glue layer, and obtaining the sand-planted paper with an abrasive layer after drying once; Step S4: Coat the abrasive layer surface of the abrasive layer of the abrasive paper with an abrasive layer, and the coating amount of the phenolic resin is 300g / m 2 , after secondary drying, super soft water sandpaper is obtained.

[0028] Example 2 This embodiment provides a method for preparing super soft water sandpaper, comprising the following steps: Preparation of composite modified silicon carbide: by weight, 6 parts of sodium lignin sulfonate are added to 400 parts of deionized water to fully dissolve, then 10 parts of silicon carbide I (average particle size of 8 μm) are added and stirred for 6 hours, the supernatant is collected by centrifugation, and dried to obtain primary modified silicon carbide; 10 parts of the primary modified silicon carbide are added to 200 parts of anhydrous ethanol and ultrasonically oscillated for 40 minutes, then 4 parts of perfluorooctyltriethoxysilane are added, and the reaction is stirred at 3000 r / min at 40°C for 4 hours. After the reaction is completed, the composite modified silicon carbide is filtered, dried, and ground to obtain the composite modified silicon carbide.

[0029] Preparation of phenolic resin compound glue: (1) In parts by weight, add 10 parts of calcium carbonate and 4 parts of dodecyl phosphate to 120 parts of deionized water, keep the temperature at 80°C for 30 minutes, filter and dry to obtain phosphorus-containing calcium carbonate; in parts by weight, add 10 parts of the phosphorus-containing calcium carbonate to 50 parts of anhydrous ethanol, ultrasonically disperse for 1 hour to obtain a suspension, add 2 parts of DL-alanine to the suspension, heat it to 75°C and stir for 1 hour, filter, wash and dry to obtain the amino-modified calcium carbonate. (2) In parts by weight, mix and stir 70 parts of phenolic resin (35 parts of phenolic phenolic resin and 35 parts of biphenyl phenolic resin), 40 parts of amino-modified calcium carbonate, 2 parts of pigment, 0.1 parts of 3-aminopropyltrimethoxysilane, 0.2 parts of Span 80, 0.2 parts of polydimethylsiloxane and 0.2 parts of leveling agent for 2 hours to obtain the phenolic resin compound glue.

[0030] Step S1: by weight, 50 parts of iron sulfate pentahydrate are added to 200 parts of deionized water to fully dissolve, then 6 parts of carbon nanotubes are added and ultrasonicated for 40 minutes, then 100 parts of hydrogen peroxide are added and stirred for reaction for 10 hours, after the reaction is completed, filter cakes are obtained by suction filtration, the filter cakes are washed with deionized water, and dried to obtain hydroxylated carbon nanotubes; 6 parts of the hydroxylated carbon nanotubes and 10 parts of isopropyl tri(dioctylphosphoyl) titanate are added to 180 anhydrous ethanol and ultrasonicated for 50 minutes, then reacted at 70°C for 10 hours, after the reaction is completed, filter cakes are suctioned, washed with anhydrous ethanol, and dried to obtain titanate-modified carbon nanotubes; 6 parts of hydroxylated carbon nanotubes are dispersed in 60 parts of ethyl acetate, then 30 parts of polyurethane are added and stirred for 2 hours, and dried to obtain modified polyurethane primer; Step S2: Coat the surface of the latex paper with a modified polyurethane primer, the coating amount of the modified polyurethane primer is 10g / m 2 , obtaining latex paper with a base glue layer; Step S3: Sand-planting the composite modified silicon carbide abrasive on the surface of the base glue layer of the latex paper with a base glue layer, and obtaining the sand-planted paper with an abrasive layer after drying once; Step S4: Coat the surface of the abrasive layer of the abrasive layer-embedded sandpaper with a phenolic resin adhesive, wherein the coating amount of the phenolic resin adhesive is 30 g / m 2 , after secondary drying, super soft water sandpaper is obtained.

[0031] Example 3 This embodiment provides a method for preparing super soft water sandpaper, comprising the following steps: Preparation of composite modified silicon carbide: In parts by weight, 8 parts of sodium lignin sulfonate are added to 450 parts of deionized water to fully dissolve, and then 15 parts of silicon carbide I (average particle size of 8 μm) are added and stirred for 7 hours, the supernatant is collected by centrifugation, and dried to obtain primary modified silicon carbide; 15 parts of the primary modified silicon carbide are added to 250 parts of anhydrous ethanol and ultrasonically oscillated for 50 minutes, and then 5 parts of perfluorooctyltriethoxysilane are added, and the reaction is stirred at 3500 r / min at 45°C for 3 hours. After the reaction is completed, the mixture is filtered, dried, and ground to obtain the composite modified silicon carbide.

[0032] Preparation of phenolic resin compound glue: (1) In parts by weight, 12 parts of calcium carbonate and 5 parts of dodecyl phosphate are added to 140 parts of deionized water, kept at a constant temperature of 82°C for 25 minutes, filtered, and dried to obtain phosphorus-containing calcium carbonate; in parts by weight, 12 parts of the phosphorus-containing calcium carbonate are added to 55 parts of anhydrous ethanol, ultrasonically dispersed for 2 hours to obtain a suspension, 3 parts of DL-alanine are added to the suspension, heated to 78°C and stirred for 1 hour, filtered, washed and dried to obtain the amino-modified calcium carbonate. (2) In parts by weight, 72 parts of phenolic resin (37 parts of phenolic phenolic resin and 35 parts of biphenyl phenolic resin), 45 parts of amino-modified calcium carbonate, 3 parts of pigment, 0.2 parts of γ-glycidyloxypropyl trimethoxysilane, 0.3 parts of Tween 60, 0.3 parts of triglycerol monostearate and 0.3 parts of leveling agent are mixed and stirred for 3 hours to obtain the phenolic resin compound glue.

[0033] Step S1: by weight, 55 parts of iron sulfate pentahydrate are added to 250 parts of deionized water to fully dissolve, then 8 parts of carbon nanotubes are added to ultrasonicate for 50 minutes, and then 110 parts of hydrogen peroxide are added to stir and react for 11 hours. After the reaction is completed, filter cakes are obtained by suction filtration, and the filter cakes are washed with deionized water and dried to obtain hydroxylated carbon nanotubes; 8 parts of the hydroxylated carbon nanotubes and 12 parts of isopropyl tri(dioctylphosphoyl) titanate are added to 190 anhydrous ethanol and ultrasonicate for 55 minutes, and then reacted at 75°C for 9 hours. After the reaction is completed, filter cakes are obtained by suction filtration, washing with anhydrous ethanol, and drying to obtain titanate-modified carbon nanotubes; 8 parts of hydroxylated carbon nanotubes are dispersed in 70 parts of ethyl acetate, and then 33 parts of polyurethane are added to stir for 3 hours and dried to obtain modified polyurethane primer; Step S2: Coat the surface of the latex paper with a modified polyurethane primer, the coating amount of the modified polyurethane primer is 50g / m 2 , obtaining latex paper with a base glue layer; Step S3: Sand-planting the composite modified silicon carbide abrasive on the surface of the base glue layer of the latex paper with a base glue layer, and obtaining the sand-planted paper with an abrasive layer after drying once; Step S4: Coat the abrasive layer surface of the abrasive layer-embedded sandpaper with a phenolic resin adhesive, wherein the coating amount of the phenolic resin adhesive is 150 g / m 2 , after secondary drying, super soft water sandpaper is obtained.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that commercially available polyurethane is used instead of modified polyurethane as the low-gluten.

[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that silicon carbide I is used as the abrasive instead of the composite modified silicon carbide.

[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that silicon carbide II is used instead of silicon carbide I to prepare the composite modified silicon carbide.

[0037] Comparative Example 4 The difference between this comparative example and Example 1 is that silicon carbide III is used instead of silicon carbide I to prepare the composite modified silicon carbide.

[0038] Comparative Example 5 The difference between this comparative example and Example 1 is that in the preparation of phenolic resin composite glue, the amount of phenol-type phenolic resin is changed to 25 parts, and the amount of biphenyl-type phenolic resin is changed to 50 parts.

[0039] Comparative Example 6 The difference between this comparative example and Example 1 is that in the preparation of phenolic resin composite glue, the amount of phenol-type phenolic resin is changed to 55 parts, and the amount of biphenyl-type phenolic resin is changed to 20 parts.

[0040] Comparative Example 7 The difference between this comparative example and Example 1 is that commercially available calcium carbonate is used instead of amino-modified calcium carbonate.

[0041] Performance Testing The water sandpaper prepared in the above examples and comparative examples was subjected to the following tests: (1) Longitudinal tensile strength test: refer to the requirements of "JB / T 7499-2023 Coated Abrasives Water-resistant Sandpaper" for testing.

[0042] (2) Water absorption test: Cut the water-treated sandpaper into 150 mm × 50 mm sample strips, weigh its mass W1 on an electronic balance, immerse it in water for 900 seconds and then take it out. Use filter paper to absorb the water stains on the surface, weigh its mass W2 on an electronic balance, and calculate the water absorption rate ρ of the water-treated sandpaper using the following formula:

[0043] Where: W1, W2 are the masses of the sample strip before and after immersion in water, in g; T is the immersion time, in s; S is the area of ​​the sample strip, in m 2 ; ρ is water absorption, unit is g / (m 2 ·s).

[0044] (3) Grinding performance test: Test according to the requirements of “JB / T 10155-2012 Test method for grinding performance of coated abrasives, emery cloth and sandpaper”.

[0045] Table 1 Performance test results

[0046] From the above performance test results, it can be seen that the water-treated sandpaper of Examples 1-3 has the best comprehensive effect, with a longitudinal tensile strength of 9.1-9.5 KN / m and a water absorption rate of 0.041-0.044 g / (m 2 ·s), no tearing or peeling occurred after the grinding performance test. This is mainly because it uses modified polyurethane as the base glue, composite modified carbonization as the abrasive, and phenolic resin containing amino-modified calcium carbonate as the glue, which effectively improves the longitudinal tensile strength of the sandpaper, reduces water absorption, and ensures good grinding performance.

[0047] The comparative examples, however, did not adopt the necessary technical solutions, resulting in significantly worse performance tests than the examples. Compared with Example 1, the comparative example 1 used commercially available polyurethane instead of modified polyurethane as the low-glue, which reduced the longitudinal tensile strength, increased the water absorption rate, and deteriorated the grinding performance. Compared with Example 1, the comparative example 2 used silicon carbide I instead of composite modified silicon carbide as the abrasive, which reduced the longitudinal tensile strength, increased the water absorption rate, and deteriorated the grinding performance. Compared with Example 1, the comparative example 3 used silicon carbide II instead of silicon carbide I to prepare composite modified silicon carbide. Since the particle size of silicon carbide II was too small, the modification effect was not good, so the longitudinal tensile strength was reduced, the water absorption rate was increased, and the grinding performance was deteriorated. Compared with Example 1, the comparative example 4 used silicon carbide III instead of silicon carbide I to prepare composite modified silicon carbide. Since the particle size of silicon carbide III was too large, The modification effect is not good, so the longitudinal tensile strength is reduced, the water absorption rate is increased, and the grinding performance is deteriorated; compared with Example 1, the amount of phenol-type phenolic resin is changed to 25 parts in the preparation of the phenolic resin compound of Comparative Example 5, and the amount of biphenyl-type phenolic resin is changed to 50 parts. Since the amount of phenol-type phenolic resin is too little, the effect is not good, so the longitudinal tensile strength is reduced, the water absorption rate is increased, and the grinding performance is deteriorated; compared with Example 1, the amount of phenol-type phenolic resin is changed to 55 parts in the preparation of the phenolic resin compound of Comparative Example 6, and the amount of biphenyl-type phenolic resin is changed to 20 parts. Since the amount of phenol-type phenolic resin is too much, the effect is not good, so the longitudinal tensile strength is reduced, the water absorption rate is increased, and the grinding performance is deteriorated; compared with Example 1, Comparative Example 7 uses commercially available calcium carbonate instead of amino-modified calcium carbonate, then the longitudinal tensile strength is reduced, the water absorption rate is increased, and the grinding performance is deteriorated. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.

[0048] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing super soft water sandpaper, characterized in that: The following steps are involved: Step S1: by weight, 50-60 parts of iron sulfate pentahydrate are added to 200-300 parts of deionized water for full dissolution, then 6-10 parts of carbon nanotubes are added for ultrasonication for 40-60 minutes, and then 100-120 parts of hydrogen peroxide are added for stirring and reaction for 10-12 hours. After the reaction is completed, filter cakes are obtained by suction filtration, and the filter cakes are washed with deionized water and dried to obtain hydroxylated carbon nanotubes; 6-10 parts of the hydroxylated carbon nanotubes and 10-14 parts of isopropyl tri(dioctylphosphoyloxy) titanate are added to 180-200 anhydrous ethanol for ultrasonication for 50-60 minutes, and then reacted at 70-80° C. for 8-10 hours. After the reaction is completed, filter cakes are washed with anhydrous ethanol and dried to obtain titanate-modified carbon nanotubes; 6-10 parts of hydroxylated carbon nanotubes are dispersed in 60-80 parts of ethyl acetate, and then 30-36 parts of polyurethane are added for stirring for 2-4 hours, and dried to obtain modified polyurethane primer; Step S2: coating the surface of the latex paper with a modified polyurethane primer to obtain a latex paper with a primer layer; Step S3: Grafting silicon carbide abrasive on the surface of the base glue layer of the latex paper with a base glue layer, and obtaining the grained sandpaper with an abrasive layer after drying once; Step S4: coating the phenolic resin adhesive on the abrasive layer surface of the abrasive layer-grafted sandpaper, and obtaining the super-soft water-based sandpaper after secondary drying.

2. The method for preparing super soft water sandpaper according to claim 1, characterized in that: The silicon carbide abrasive is composite modified silicon carbide; The preparation method of the composite modified silicon carbide comprises: adding 6 to 10 parts of sodium lignin sulfonate to 400 to 500 parts of deionized water by weight to fully dissolve, then adding 10 to 20 parts of silicon carbide (average particle size is 1 to 10 μm) and stirring for 6 to 8 hours, collecting the supernatant by centrifugation, and drying to obtain primary modified silicon carbide; adding 10 to 20 parts of the primary modified silicon carbide to 200 to 300 parts of anhydrous ethanol and ultrasonically oscillating for 40 to 60 minutes, then adding 4 to 6 parts of perfluorooctyl triethoxysilane, stirring and reacting at a speed of 3000 to 4000 r / min at 40 to 50° C. for 2 to 4 hours, and after the reaction is completed, filtering, drying, and grinding to obtain the composite modified silicon carbide.

3. The method for preparing super soft water sandpaper according to claim 1, characterized in that: The preparation method of the phenolic resin compound glue comprises: mixing 70-75 parts of phenolic resin, 40-50 parts of amino-modified calcium carbonate, 2-3 parts of pigment, 0.1-0.3 parts of coupling agent, 0.2-0.4 parts of penetrant, 0.2-0.4 parts of defoamer and 0.2-0.4 parts of leveling agent for 2-4 hours to obtain the phenolic resin compound glue.

4. The method for preparing super soft water sandpaper according to claim 3, characterized in that: The phenolic resin is a phenolic phenolic resin and a biphenyl phenolic resin; the mass ratio of the phenolic phenolic resin to the biphenyl phenolic resin is (1-2):

1.

5. The method for preparing super soft water sandpaper according to claim 3, characterized in that: The preparation method of the amino-modified calcium carbonate comprises: adding 10-15 parts of calcium carbonate and 4-6 parts of dodecyl phosphate to 120-150 parts of deionized water by weight, maintaining the water at a constant temperature of 80-85°C for 20-30 minutes, filtering, and drying to obtain phosphorus-containing calcium carbonate; adding 10-15 parts of the phosphorus-containing calcium carbonate to 50-60 parts of anhydrous ethanol by weight, performing ultrasonic dispersion for 1-2 hours to obtain a suspension, adding 2-4 parts of DL-alanine to the suspension, heating the suspension to 75-80°C, stirring the suspension for 0.5-1 hour, and obtaining the amino-modified calcium carbonate by suction filtration, washing, and drying.

6. The method for preparing super soft water sandpaper according to claim 3, characterized in that: The coupling agent is selected from any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane, or a combination of at least two thereof.

7. The method for preparing super soft water sandpaper according to claim 3, characterized in that: The osmotic agent is selected from any one of Span 60, Span 80, Tween 60, or a combination of at least two thereof.

8. The method for preparing super soft water sandpaper according to claim 3, characterized in that: The defoaming agent is selected from any one of tributyl phosphate, polydimethylsiloxane, and tripolyglycerol monostearate, or a combination of at least two thereof.

9. The method for preparing super soft water sandpaper according to claim 3, characterized in that: The coating amount of the modified polyurethane primer is 10-100 g / m 2 The coating amount of the phenolic resin is 30~300g / m 2 .

10. A super soft water sandpaper, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A water-resistant sandpaper and its preparation method

    CN110919559B

  • Latex abrasive base paper and preparation method and application thereof

    CN107034720A

  • High-strength and high-performance compound grinding sheet and manufacturing method thereof

    CN107081688A

  • Formula of cutting-grinding dual-purpose resin grinding wheel and processing method

    CN107363743A

  • Ceramic microcrystalline fused alumina steel paper coated abrasive tool and manufacturing method thereof

    CN107571165A

Cited By

  • Laser edge sealing strip and production process thereof

    CN120424392A